Focus on Bose condensation phenomena in atomic and solid state physics - Iacopo Carusotto; Jörg Schmiedmayer; Luis Viña (New Journal of Physics, 2013)
This editorial provides a short overview of the focus issue on Bose condensation phenomena in atomic and solid state physics sponsored by the POLATOM ESF Research Networking Programme.